Consumers’ innovativeness and acceptance towards use of financial technology in Pakistan: extension of the UTAUT model - Imran Mehboob Shaikh; Hanudin Amin (ResearchGate, 2024)
Purpose – This paper aims to examine the factors that influence bank customers’ acceptance towards FinTech using the unified theory of acceptance and use of technology (UTAUT) model. Design/methodology/approach – A survey was carried out, and a judgemental sampling method was used. Moreover, over 200 responses were gathered from individuals that were bank account holders. Besides, the literature on the factors that influence an individual acceptance towards FinTech using the UTAUT model was also reviewed as an effort to contribute towards the factors that are significant in predicting the acceptance of FinTech services. Findings – The results of the study revealed that performance expectancy and effort expectancy are the main factors in determining the acceptance of FinTech services. Moreover, consumer innovativeness plays an important role in the acceptance of FinTech by bank users. In contrast, social influence and facilitating conditions were not the determinants of FinTech acceptance in Pakistan. Research limitations/implications – This study not only contributed to the theoretical extensions but also to practical implications, which would benefit the community of FinTech service providers in Pakistan. Practical implications – The limitations of this study were two but are not limited to, firstly, the respondents which were taken among bank customers in Pakistan, confining its contribution to the narrowed perspective of Pakistan. Besides, this study also considers its contributions towards the use of the UTAUT in which the factors examined were specific, which may elucidate that the generalization of the findings only includes FinTech, where the UTAUT comes into play. This study is an eye-opener for the merging perspective of both the UTAUT and FinTech. Originality/value – UTAUT is extended in the context of FinTech. Consumer innovativeness is incorporated in the context of the UTAUT model. Consumer innovativeness is yet to be tested and for that this study is a useful reference for academicians, policymakers and future researchers.